Primary pulmonary lymphoma in Peru - Requena, EDA (2023)
Objective: To describe the clinical features, imaging, pathology and management of patients with primary pulmonary lymphoma (PPL). Methodology: This is a case series study involving a retrospective analysis of 24 patients diagnosed with PPL between the years 2000-2019 at Instituto Nacional de Enfermedades Neoplásicas in Lima, Perú. Results: 73.9% of patients were male. Cough (78.3%) and weight loss (56.5%) were the most frequent clinical features. Dyspnoea and elevated values of DHL and B2 microglobulin were frequently altered in advanced stages. Diffuse large B cell lymphoma (DLBCL) represented 47.8% of the cases and the most common radiologic alterations were a mass (60%) and consolidation with air bronchogram (60%). The most utilised treatment was chemotherapy alone (60%). Three patients received only surgery. Median survival was 30 months. Five overall survival was 45%, and up to 60% in the case of mucosa-associated lymphoid tissue lymphoma. Conclusion: PPL is infrequent. Clinical features are unspecific and the principal finding is a mass, nodule or consolidation with air bronchogram. Definitive diagnosis needs biopsy and immunohistochemistry. There is no standard treatment, it depends on histology type and stage.